Overeducation Among University Graduates in STEM Fields in Peru - Mendoza-Pumapillo, José Enrique; Ortiz-Chávez, Miguel Ángel; Dilas-Jiménez, Josué Otoniel (Sociedad y Economía, 2024)
Introduction Investment in STEM education and its relationship with salary returns is inconsistent, highlighting the need to study the characteristics and effects of the mismatch between these two variables. Objective To identify the factors that explain the mismatch between education and employment among university graduates in science, technology, engineering, and mathematics (STEM) fields, as well as its effects on wages. Methodology The study used data from Peru’s 2014 National Survey of University Graduates and Universities, measuring mismatch through the self-assessment method. A Partial Generalized Ordered Logit Model was applied to analyze the determinants associated with mild and severe mismatch levels, with emphasis on the latter. Additionally, wage penalties associated with mismatch were estimated using the Propensity Score Matching technique. Results The findings show that 69% of STEM graduates experience employment mismatch, one of the highest rates in Latin America and higher than those reported in developed countries. Conclusions The main determinants of severe mismatch are the graduates’ personal characteristics, origin, and educational trajectory. The wage penalty for mismatched STEM graduates was approximately 24% compared to those adequately employed, exceeding the penalties observed in Europe, Asia, and North America.